Phygital Heritage Experiences in Refugee Attica - Antoniou, Angeliki; Lampada, Despoina; Kamara, Afroditi; Kyriaki-Manessi , Daphne (Journal of Integrated Information Management, 2024)
The Greco-Turkish war’s aftermath led to a significant refugee crisis in 1922, with over 1.5 million fleeing Asia Minor for safety in Greece. The Digistoryteller project aims to document and share narratives of these refugees’ struggles to establish homes in Attica, using digital storytelling and crowdsourcing features. This project, through its database and mobile apps, allows for city exploration and contributions from experts and the public. A key focus of the project is the concept of "phygitality," which combines physical and digital experiences. Phygitality encompasses various combinations, including augmented reality, 3D printing, and holograms. In cultural heritage, phygitality offers new ways to engage with historical sites and enhance cultural experiences. Different phygital products developed within the framework of the project will be presented. In the case of Vyronas, a municipality in Attica founded as the first urban refugee settlement, the project introduces phygital objects like paper reconstructions of historical buildings. These objects, like the Old Town Hall, provide educational and touristic value by allowing users to assemble them and access augmented reality information about the building’s history. Initial user testing has shown promising results, with plans to integrate these objects into educational programs and museum shops. The municipality of Vyronas intends to produce these objects for both educational and touristic purposes